Wernekink commissure syndrome: clinico-radiological criteria - S, Sheetal; S, Amith Kumar; Thomas, Reji (Nepal Journal of Neuroscience, 2020)
Introduction: Wernekink commissure syndrome is a rare midbrain syndrome selectively affecting the Wernekink commissure, characterized by bilateral cerebellar ataxia and eye movement disorders, especially internuclear ophthalmoplegia. This article aims at proposing clinico-radiological criteria for Wernekink commissure syndrome with review of the neural circuitary responsible, to aid in recognition and reporting. Methods: This was a prospective study conducted at Department of Neurology, at Pushpagiri institute of medical sciences and research centre, Thiruvalla, Kerala, India, over a period of 5 years among patient with pure midbrain syndromes. All patients with pure midbrain infarction were studied. Subjects presenting with clinical features of Wernekink commissure syndrome were shortlisted and were assessed by investigators independently. Neuroradiology was assessed by investigators 1 and 2, independently. The demographic profile, risk factors, clinical features, neuroimaging findings and outcomes were analysed using SPSSv21. Results: Details of 43 subjects with pure midbrain stroke were included in the study. 8 had clinical features of Wernekink commissure syndrome. The most common findings were bilateral ataxia and unilateral or bilateral internuclear ophthalmoplegia. None of our patients had palatal tremor. Unilateral caudal paramedical infarction was seen on MRI in 5 patients, whereas it was bilateral in 3 patients. Conclusions: The proposed clinico-radiological criteria consisting of all of the essential criteria (Ipsilateral internuclear ophthalmoplegia, Unilateral or bilateral ataxia and Neuroradiological evidence of Caudal midbrain involvement) with or without one among the supportive criteria (Rubral Tremor, Palatal myoclonus) can safely point at a diagnosis of Wernekink commissure syndrome.